Anaplastic thyroid cancer with life-threatening symptoms in an older female - a case report - Pawęska, Wojciech; Dominik, Hanna; Dominik, Barbara (Journal of Education, Health and Sport, 2023)
Introduction: Anaplastic thyroid cancer, also called undifferentiated, is an uncommon and highly aggressive thyroid neoplasm that usually occurs in patients above 60 years of age (mean 65 years). Incidence is about 1-2 cases per million persons a year. [11] It accounts for 1-2% of thyroid cancer cases and probably develops from previously differentiated thyroid neoplasms. [1] Mutations of TP53 gene are most common and exist in 17-80% of patients. Other frequently mutated genes are RAS, BRAF and β-catenin. [3] The metastatic spread tends to occur through hematogenous and lymphatic pathways. The neoplasm presents as a rapidly enlarging neck mass that can cause compression on the neck structures giving symptoms such as dysphagia and dyspnea. Patients with established diagnosis of anaplastic thyroid cancer have very poor prognosis. Mean survival time of patients after confirmed diagnosis is 3 to 6 months and 5-year survival rate is estimated to be 5-14%. [2] Aim: The aim of this study is to portray the clinical presentation, course and complications of a patient suffering from anaplastic thyroid cancer. This case report includes performed procedures and implemented treatment. Description of the case: We present a case of an 87-year-old female that was admitted to the hospital with a large thyroid mass, symptoms of dysphagia, dyspnea and significant weight loss. Clinical picture was suspicious of anaplastic thyroid cancer. Further workup included laboratory testing, imaging and FNA biopsy. Surgical procedure of tracheostomy was conducted due to life-threatening dyspnea with consecutive patient’s monitoring in Intensive Care Unit. After achieving clinically stable state the patient was transferred to Clinical Department of Radiotherapy where palliative radiotherapy was initiated.